Influenza Virus and Glycemic Variability in Diabetes: A Killer Combination? - Hulme, Katina D.; Gallo, Linda A.; Short, Kirsty R. (Frontiers in Microbiology, 2017)
Following the 2009 H1N1 influenza virus pandemic, numerous studies identified a link between diabetes mellitus and severe influenza. Typically, influenza virus is a self-limiting infection. However, in individuals who have a pre-existing chronic illness, such as diabetes mellitus, severe disease can develop. Here, we discuss the latest clinical and experimental evidence for the role of diabetes in severe influenza infections. We explore the possible mechanisms that underlie this synergy and highlight the as yet unexplored role that blood glucose oscillations may play in disease development. Diabetes is one of the world’s fastest growing chronic diseases and influenza virus represents a constant and pervasive threat to human health. It is therefore imperative that we understand how diabetes increases influenza severity in order to mitigate the burden of future influenza epidemics and pandemics.